Determination of Effects of Genetic Diversity of Oenococcus Oeni and Physicochemical Characteristicson Malolactic Fermentation Across Chilean Vineyards, Using Multivariate Methods - Ganga-Munoz, M; Godoy-Olivares, L (Journal of Pure and Applied Microbiology, 2018)
After alcoholic fermentation, Oenococcus oeni is the protagonist that carry out malolactic fermentation in order to improve the quality of wine. However, the effectiveness of malolactic fermentation varies according to intraspecific diversity of O. oeni at a genetic level and physicochemical concentrations of intrinsic factors. In this study, we assessed both components by isolating O. oeni from three Chilean vineyards (Maipo, Colchagua y Curicó) and measuring intrinsic components, such as biogenic amines and amino acids, during malolactic fermentation. Both data were condensed and then processed with Multivariate using the statistical method of correspondence analysis. The genetic data was clustered using the RAPD-PCR molecular method, and the physicochemical analysis was carried out using chromatography techniques. Isolation of O. oeni species and genetic diversity results between the vineyards revealed that O. oeni strains cluster according to its geographical origin, with strains similarity higher than 60% of all the samples. The wines of each valley could be characterized by the presence or absence of biogenic amines, and final correspondence analysis showed that there is a differentiation of strains between the studied Valleys, also confirming the accomplishment of the malolactic fermentation in the wines analyzed. © 2018 Journal of Pure and Applied Microbiology. All rights reserved.